The Kerala model in the time of COVID19: Rethinking state, society and democracy. (January 2021) - Chathukulam, Jos; Tharamangalam, Joseph
Highlights: Kerala's pandemic management has been a decisive test of the "Kerala model of development". Behind Kerala's relative success were robust public institutions, the legacy of the "Kerala model" built over many years. This pandemic shows that even a participatory social democratic state face tough challenge in managing crises and guaranteeing basic security. Adversarial politics and absence of consensus-based democratic approach led to the surge in Covid 19 in Kerala. Abstract: Kerala, a small state in South India, has been celebrated as a development model by scholars across the world for its exemplary achievements in human development and poverty reduction despite relatively low GDP growth. It was no surprise, then, that the Covid 19 pandemic that hit Kerala before any other part of India, became a test case for the Kerala model in dealing with such a crisis. Kerala was lauded across the world once again as a success story in containing this unprecedented pandemic, in treating those infected, and in making needed provisions for those adversely affected by the lockdown. But as it turned out, this celebration was premature as Kerala soon faced a third wave of Covid 19 infections. The objective of this paper is to examine Kerala's trajectory in achieving the success and then confronting the unanticipated reversal. It will examine the legacy of the Kerala model such as robust and decentralized institutions and provisions for healthcare, welfare and safety nets, and especially the capacity of a democratic state working in synergy with civil society and enjoying a high degree of consensus and public trust. It will then examine the new surge of the virus and attempts to establish if this was due to any mistakes made by the state or some deficits in its model of "public action" that includes adversarial politics having a disruptive tenor about it. We will conclude by arguing that the Kerala model is still relevant, and that it is still a model in motion.